2019
DOI: 10.1111/jce.14015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the amount and patterns of late enhancement in Chagas disease according to the presence and type of ventricular tachycardia

Abstract: Background Ventricular tachycardia (VT) is one of the main predictors of mortality in Chagas cardiomyopathy (CC). Although the substrate of sustained and nonsustained‐VT (NS‐VT) seems to be the same, little is known about the distribution of late enhancement (LE). Our aim was to compare the clinical findings and the amount and patterns of LE in Chagas disease according to the presence and type of VT. Methods and Results Magnetic resonance imaging was performed in 54 Chagas seropositive patients: 8 indeterminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
“…VA were investigated in three studies involving LGE. Two studies established that the involvement of two or more transmural segments was associated with a higher risk of ventricular tachycardia (VT) [6,9]. Mello et al [6] found that the group of patients with VT had a relative 4.1 risk (95% CI 1.06-15.68) of having two or more segments with LGE with a transmural distribution, compared to those without VT.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%